2019
DOI: 10.22564/rbgf.v37i4.2013
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectrical Signatures and their Relationships with the Lateritic Horizons: A Case Study of the N4EN Mine’s Iron Cave, Carajás Complex, Brazil

Abstract: The Brazilian speleological heritage is protected by laws, and every region where caves are present requires scientific studies to assist in environmental licensing. In the context of mining in iron formations, the near-surface geophysical studies using electroresistivity survey were performed in the cave N4E-0022, located at the N4EN iron mine, Carajás Complex, northern Brazil. The near-surface geophysical surveys generated continuous images that enhanced the lithostructural mapping of the lateritic profile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The literature published in the past revealed that various researchers used the ERT technique very effectively to delineate sinkholes, potholes, old abandoned goaves, cavities, voids, underground galleries/workings and so on (Abu‐Shariah, 2009; Das & Mohanty, 2016; Das et al., 2017; Ortega et al., 2010; Van Schoor, 2002; Zhou et al., 2004; Bharti, Pal, Priam, Kumar, et al., 2016; Bharti, Pal, Priam, Pathak, et al., 2016; Bharti et al., 2016c; Arjwech et al., 2021; Barbosa et al., 2020; Bharti et al. 2021; Bhattacharya & Shalivahan, 2016; Fargier et al., 2017; Nthaba et al., 2020; Prakash & Bharti, 2022; Prakash et al., 2022; Prosdocimi et al., 2019; Samanlangi, 2018; Bharti, Singh, et al., 2022; Bharti, Prakash, et al., 2022). A recent study by Saurabh et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature published in the past revealed that various researchers used the ERT technique very effectively to delineate sinkholes, potholes, old abandoned goaves, cavities, voids, underground galleries/workings and so on (Abu‐Shariah, 2009; Das & Mohanty, 2016; Das et al., 2017; Ortega et al., 2010; Van Schoor, 2002; Zhou et al., 2004; Bharti, Pal, Priam, Kumar, et al., 2016; Bharti, Pal, Priam, Pathak, et al., 2016; Bharti et al., 2016c; Arjwech et al., 2021; Barbosa et al., 2020; Bharti et al. 2021; Bhattacharya & Shalivahan, 2016; Fargier et al., 2017; Nthaba et al., 2020; Prakash & Bharti, 2022; Prakash et al., 2022; Prosdocimi et al., 2019; Samanlangi, 2018; Bharti, Singh, et al., 2022; Bharti, Prakash, et al., 2022). A recent study by Saurabh et al.…”
Section: Introductionmentioning
confidence: 99%
“…ERT is a versatile tool for mapping of subsurface features like voids, cavities, underground galleries/tunnels (air‐or water‐filled) and so on, where high contrast in resistivity is leveraged to delineate the features very easily. In ERT study, high‐resolution information on subsurface resistivity variation depends on the data quality, data density, choices of electrode configuration and electrode spacing (Aizebeokhai, 2010; Barbosa et al., 2020; Bharti, Pal, Saurabh, Kumar, et al., 2019; Bharti, Pal, Saurabh, Singh, et al., 2019; Cardarelli et al., 2010, 2014; Chandra et al., 2008; Fargier et al., 2017; Giao et al., 2003; Horo et al., 2020; Kumar, 2012; Kumar et al., 2021; Leucci, 2006; Loke, 2000; Nthaba et al., 2020; Prosdocimi et al., 2019; Samanlangi, 2018; Singh, 2013; Singh et al., 2004; Ward, 1989).…”
Section: Introductionmentioning
confidence: 99%